2021
DOI: 10.1038/s41467-021-25252-9
|View full text |Cite
|
Sign up to set email alerts
|

PARylation prevents the proteasomal degradation of topoisomerase I DNA-protein crosslinks and induces their deubiquitylation

Abstract: Poly(ADP)-ribosylation (PARylation) regulates chromatin structure and recruits DNA repair proteins. Using single-molecule fluorescence microscopy to track topoisomerase I (TOP1) in live cells, we found that sustained PARylation blocked the repair of TOP1 DNA-protein crosslinks (TOP1-DPCs) in a similar fashion as inhibition of the ubiquitin-proteasome system (UPS). PARylation of TOP1-DPC was readily revealed by inhibiting poly(ADP-ribose) glycohydrolase (PARG), indicating the otherwise transient and reversible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 56 publications
3
25
0
Order By: Relevance
“…This finding coincided with the discovery in yeast of the first DPC protease, Wss1 (Stingele et al, 2014). (Liu et al, 2021;Krastev et al, 2022) Pli1 SUMO-targeted ubiquitylation pathway TOP1-DPC (Steinacher et al, 2013) Nse2 SUMO-targeted ubiquitylation pathway TOP1-DPC (Heideker et al, 2011) PARylation PARP1 PARP1 auto-PARylation limits PARP1 trapping, recruits PTUbLs or deubiquitylation enzymes PARP1-trapping (Prasad et al, 2014;Steffen et al, 2016;Gatti et al, 2020;Kruger et al, 2020) TOP1-DPC (Sun et al, 2021) PTM Readers/Effectors Ubiquitylation Proteasome DPC proteolysis M.HpaII-DPC (Larsen et al, 2019) DNMT1-DPC (Liu et al, 2021) TOP1-DPC (Desai et al, 1997;Mao et al, 2000b;Desai et al, 2003;Zhang et al, 2004;Lin et al, 2008;Sordet et al, 2008;Kerzendorfer et al, 2010;Heideker et al, 2011;Steinacher et al, 2013;Nie et al, 2017;Sun et al, 2020;Sun et al, 2021) TOP2-DPC (Mao et al, 2001;Wei et al, 2017;Sun et al, 2020) TOP3B-DPC (Saha et al, 2020) Polβ-DPC (Quinones et al, 2015;Quinones et al, 2020) PARP1-trapping (Prasad et al, 2019;Gatti et al, 2020) Flp-DPC (Ma et al, 2019) HMCES-DPC (Mohni et al, 2019) SPRTN a DPC proteolysis M.HpaII-DPC (Larsen et al, 2019) TOP1-DPC (Vaz et al, 2016;Maskey et al, 2017) TOP2-DPC (Lopez-Mosqueda et al, 2016;…”
Section: Replication-coupled Dna-protein Crosslink Ubiquitylation By ...supporting
confidence: 65%
See 1 more Smart Citation
“…This finding coincided with the discovery in yeast of the first DPC protease, Wss1 (Stingele et al, 2014). (Liu et al, 2021;Krastev et al, 2022) Pli1 SUMO-targeted ubiquitylation pathway TOP1-DPC (Steinacher et al, 2013) Nse2 SUMO-targeted ubiquitylation pathway TOP1-DPC (Heideker et al, 2011) PARylation PARP1 PARP1 auto-PARylation limits PARP1 trapping, recruits PTUbLs or deubiquitylation enzymes PARP1-trapping (Prasad et al, 2014;Steffen et al, 2016;Gatti et al, 2020;Kruger et al, 2020) TOP1-DPC (Sun et al, 2021) PTM Readers/Effectors Ubiquitylation Proteasome DPC proteolysis M.HpaII-DPC (Larsen et al, 2019) DNMT1-DPC (Liu et al, 2021) TOP1-DPC (Desai et al, 1997;Mao et al, 2000b;Desai et al, 2003;Zhang et al, 2004;Lin et al, 2008;Sordet et al, 2008;Kerzendorfer et al, 2010;Heideker et al, 2011;Steinacher et al, 2013;Nie et al, 2017;Sun et al, 2020;Sun et al, 2021) TOP2-DPC (Mao et al, 2001;Wei et al, 2017;Sun et al, 2020) TOP3B-DPC (Saha et al, 2020) Polβ-DPC (Quinones et al, 2015;Quinones et al, 2020) PARP1-trapping (Prasad et al, 2019;Gatti et al, 2020) Flp-DPC (Ma et al, 2019) HMCES-DPC (Mohni et al, 2019) SPRTN a DPC proteolysis M.HpaII-DPC (Larsen et al, 2019) TOP1-DPC (Vaz et al, 2016;Maskey et al, 2017) TOP2-DPC (Lopez-Mosqueda et al, 2016;…”
Section: Replication-coupled Dna-protein Crosslink Ubiquitylation By ...supporting
confidence: 65%
“…While several studies initially reported that TOP1-DPCs are PARylated by PARP1 in vitro , the outcome of this PARylation in cells was largely unknown ( Malanga and Althaus, 2004 ; Yung et al, 2004 ; Park and Cheng, 2005 ). A recent work showed that TOP1-PARylation exhibits an adverse effect on TOP1-DPCs compared to its effect on PARP1 trapping ( Sun et al, 2021 ). By inhibiting poly (ADP-ribose) glycohydrolase (PARG), sustained PARylation on TOP1-DPCs was shown to recruit the deubiquitylating enzyme USP7 to remove ubiquitylation on TOP1-DPCs, thus preventing their proteasomal degradation ( Sun et al, 2021 ) ( Figure 1I ).…”
Section: Parylation As An Emerging Post-translational Modification On...mentioning
confidence: 99%
“…Nucleic-acid excision pathways for TOP1 and/or TOP2 include excision by the endonucleases MRE11, CtIP and XPF–ERCC1, or excision by tyrosyl-DNA phosphodiesterase 1 (TDP1) and TDP2 (step 4). b | TDP1 is activated by poly(ADP-ribose) polymerase 1 (PARP1) 268 , 269 , 275 , and upon cleaving DNA leaves a 3′-phosphate that is further processed by polynucleotide kinase phosphatase (not shown). TDP2 leaves a 5′-phosphate that can be directly ligated or extended by DNA polymerases (not shown).…”
Section: Topoisomerases and Genome Instabilitymentioning
confidence: 99%
“… 265 ). TDP1 activity is also controlled by its SUMOylation 266 , its phosphorylation by ATM and DNA-PK 267 , and its recruitment by poly(ADP-ribose) polymerase 1 (PARP1) 268 , 269 . ATM-deficient mice exhibit endogenous accumulation of TOP1-DPCs and neurodegeneration 250 .…”
Section: Topoisomerases and Genome Instabilitymentioning
confidence: 99%
“…For example, studies have shown that PARylation mediates DNA repair by reshaping chromatin into an open conformation (Poirier et al, 1982). In addition, PARylation recruits USP7, a deubiquitinating enzyme, to topoisomerase I DNA‐protein cross‐links (TOP1‐DPCs) and reverses ubiquitination of TOP1‐DPCs, indicating that PARylation involves in the repair of DPCs (Sun et al, 2021). Furthermore, poly(ADP‐ribose) polymerase 1 (PARP1) has been shown to prevent alkylation and oxidative damage of DNA in colorectal cancer, but it has also been shown to promote inflammation‐driven colorectal tumor progression (Dörsam et al, 2018).…”
Section: Figurementioning
confidence: 99%